2007
DOI: 10.1109/robot.2007.363812
|View full text |Cite
|
Sign up to set email alerts
|

The design of a tethered aerial robot

Abstract: This paper describes the design and modeling of a robot that swings on the end of a tether. Its height above the ground is controlled by the length of the tether. Its location on a spherical shell at the end of the tether is controlled by a pair of ducted fans. The vertical orientation of its body is determined by the point at which the horizontal thrust force acts relative to the centre of gravity (cog). The system acts like a double pendulum with two modes of natural movement. It is modeled with coordinate f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…A tethered aerial robot presented in (McKerrow and Ratner 2007), of which the working unit is suspended on a single cable and equipped with two ducted fan actuators. A similar but simplified concept is the Winch-Bot that is presented in (Cunningham and Asada 2009).…”
Section: Concept Of the Structural Designmentioning
confidence: 99%
“…A tethered aerial robot presented in (McKerrow and Ratner 2007), of which the working unit is suspended on a single cable and equipped with two ducted fan actuators. A similar but simplified concept is the Winch-Bot that is presented in (Cunningham and Asada 2009).…”
Section: Concept Of the Structural Designmentioning
confidence: 99%
“…Therefore, the design of dynamic models from space robots has been increasingly drawn into attention [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…With regard to significance of topic of this research, to date numerous activities have been conducted at the area of optimization of UAVs via nonlinear controllers, so that there are numerous ways to control an UAVs [4,7,8]. Use of fuzzy logic regarding capabilities of this method in controlling nonlinear systems is one way to control UAVs.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the use of tethers has advantages in applications such as Urban Search and Rescue (USAR), reconnaissance, landmine detection, bomb disposal, planetary exploration, sewerage and under-water exploration (Fukushima et al 2000, Abel 1994, P.J. McKerrow et al 2007). Fukushima et al (2000) demonstrated that tethers can be used for climbing steep slopes (cliff-climbing) and for extracting robots when stuck in debris.…”
Section: Introductionmentioning
confidence: 99%